2007
DOI: 10.1158/1055-9965.epi-07-0033
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Modeling of Occupational Exposure to Polycyclic Aromatic Hydrocarbons with Biomarkers of Exposure and Effect

Abstract: In regulatory toxicology, the dose-response relationship between occupational exposure and biomarkers is of importance in setting threshold values. We analyzed the relationships between occupational exposure to polycyclic aromatic hydrocarbons (PAH) and various biomarkers of internal exposure and DNA damage with data from 284 highly exposed male workers. Personal exposure to phenanthrene and other PAHs was measured during shift and correlated with the sum of 1À, 2+9À, 3À, and 4-hydroxyphenanthrenes in post-shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
1
12
2
Order By: Relevance
“…1,2) of target PAHs having established exposure limits were well below those limits (Table 1). By comparison, the mean phenanthrene concentration reported for a study population of 284 workers 'highly exposed' to PAHs during the manufacture of refractory products (graphite electrode production, coke oven operation, tar distillation, and steel production) was 4.81 μg m −3 (Pesch et al, 2007), while it ranged from ~5 to 9 μg m −3 in this study. In another cross-industry study (Unwin et al, 2006), 8-h time-weighted average (TWA) concentrations of BaP ranged from <0.01 to 6.21 μg m −3 , with a geometric mean of 0.036 μg m −3 .…”
Section: Resultscontrasting
confidence: 56%
“…1,2) of target PAHs having established exposure limits were well below those limits (Table 1). By comparison, the mean phenanthrene concentration reported for a study population of 284 workers 'highly exposed' to PAHs during the manufacture of refractory products (graphite electrode production, coke oven operation, tar distillation, and steel production) was 4.81 μg m −3 (Pesch et al, 2007), while it ranged from ~5 to 9 μg m −3 in this study. In another cross-industry study (Unwin et al, 2006), 8-h time-weighted average (TWA) concentrations of BaP ranged from <0.01 to 6.21 μg m −3 , with a geometric mean of 0.036 μg m −3 .…”
Section: Resultscontrasting
confidence: 56%
“…We found a tendency for positive correlation between urinary 1-OHP and 8-OH-dG after adjusting for gender, age, BMI, smoking status and drinking habit (p=0.070). However, some studies reported that there was no relationship between urinary 1-OHP and 8-OH-dG 19,34) . The first possible reason for these conflicting results is the different levels of internal exposure to PAHs.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between PAH exposure and DNA damage measured by Comet assay was not consistent among studies. In some studies 19,20 , there was no correlation between PAH exposure and DNA damage by Comet assay. However, in a paper by Gamboa and colleagues, a significant difference in tail length which measured by Comet assay to detect DNA damage between children exposed to high levels of PAH and children exposed to low levels of PAH was reported 21 .…”
Section: Resultsmentioning
confidence: 96%